CONJOINT ANALYSIS OF CHOICE ATTRIBUTES AND MARKET SEGMENTATION OF RURAL TOURISTS IN KOREA - 윤희정 (한국농촌경제연구원, 2009)
This study aims to analyze the attributes considered in choosing rural sites for tourism purposes by city dwellers and the market segmentation of rural tourism from a rural tourism demand perspective. For this purpose, this study investigates the attributes of rural areas considered in the selection of rural tourism destinations by urban dwellers using a conjoint model as a stated preference model. Based on literature reviews, two questionnaire surveys are conducted. The first questionnaire survey is performed in the 4 cities of Seoul, Daejeon, Suwon and Chuncheon with 408 urban residents. The second questionnaire survey is performed in the 5 cities of Seoul, Chuncheon, Daejeon, Cheonju and Busan with about 1,060 urban residents. The study results suggest that according to part-worth and vector models, the most important attributes in selecting rural areas for tourism are experience programs and facility convenience. The fitness level of the model ranges from 0.917 to 0.986, which is very significant. Among the 5 attribute's levels, the rural residents' obliging service, the traditional and the ecological programs and the facilities about information and accommodation are more critical factors than other levels. Utilities of each level decrease as cost and arrival time increase. Regarding the result of market segmentation, respondents having intention to visit can be divided into 4 groups; (1) facility/program-oriented group, (2) service-oriented group, (3) time-oriented group, and (4) simple participants group. These results can provide insightful information for regional planning strategies, such as selection of market segment type and the key factor of facility and space planning.
Keywords: ural tourism; rural leisure; choice attributes; market segmentation of rural tourism; regional planning; ural tourism; rural leisure; choice attributes; market segmentation of rural tourism; regional planning